MELAYANI DENGAN HATI KEPEMIMPINAN PASTORAL DALAM MENYELESAIKAN KONFLIK GEREJA - Samuel W.L. Wanget; Merri Yollanda Menaheside; Jenifer Theresia Paulus; Incha Lahimade Kasalang (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2025)
Conflict in church life is often a challenge that spiritual leaders must face. In situations like these, pastoral leadership plays a crucial role in resolving emerging problems wisely and compassionately. This article aims to explore the concept of pastoral leadership in handling church conflicts through a serving approach with the heart. This approach emphasizes values ​​such as empathy, honest communication, and a commitment to maintaining peace despite differences. With an approach based on love, pastoral leaders are expected to be able to guide congregations towards reconciliation, strengthen relationships within the church community, and strengthen the foundation of their faith. This article also discusses various leadership strategies and principles that can be applied to resolve conflicts in accordance with Christian values, thereby encouraging harmony and unity in the church body.